(untitled) (CAHIERS MAGELLANES-NS, 2024)
Vitiligo is an acquired disorder of depigmentation which occurs as white macules on skin andmay result in substantial stigmatization and psychological stress. Although treatment options exist, acure for this disease has yet to be discovered.